What attributes do existing web blog need? - Lin, Yu-Ling; Lin, Hong-Wen; Hung, Yu-Ting (Archives of Business Research, 2018)
Blog is an on online diary which is a personal record through webpages which includes the functions of automatic exchange, immediate updating, casual posting, and link exchange. People not only can type posts and upload their pictures to their web albums but also record their daily life with the web space instead of writing in the diary. However, the blog which users want is provided with the functions and attributes or the final value which users want and will pursue while using their blogs. Both of these are research questions which need to be further discussed. Thus, this research adopts means-end chains as the theoretical basis and uses attributes-consequences-values as the interview structure which deeply investigates the needs of blog users. The research results showed that users think according to the sequence, important attributes of Blogs are blog writing, photo album, personalization, special functions, discussion/messages/reply. Hierarchical value map is further drawn to explain above attributes according to the interview result. This research aims on understanding of blog users’ use factor and needs and expect that the research results can assist dealers of blog platforms to continuously develop and improve functions and the quality of platforms to provide blog platforms which meet users’ need more.